BUDAYA DALAM LINTASAN SEJARAH: BOOMING NONTON BIOSKOP DI PADANG TEMPO DULU - Meri Erawati (LPPM Universitas PGRI Sumatera Barat, 2015)
This article discusses the existence of cinema as entertainment for the people in Padang during the period 1970s to 2000s. Cinema is a mass entertainment and can be enjoyed by all the community at that time. Cinema became a phenomenal because the movies have become part of people's lifestyles. Cinema furor enlivened by promotions to attract people to come to the cinema through flyers, posters, banners and advertisements in the mass media. The development of technology led to the existence of cinema began to be replaced by the presence of new entertainment media such as television and media screenings of other films such as VCD players so that the film is no longer only be enjoyed in the cinema. Cinema audience popularity and dynamics as well as aspects related to cinema in 1970 this will be discussed within this article.